A Rotated Dynamic Nelson‐Siegel Model. (19th June 2017) - Nyholm, Ken
Abstract : I show how to rotate the factor structure of the well‐known Dynamic Nelson‐Siegel yield‐curve model to enable direct parametrization of the short rate process. This makes it easy to calculate model‐implied term premia and to integrate macroeconomic variables into the model in a Taylor‐rule‐type fashion.